THE CIRCUMSTANCES OF THE EXACT USE OF TERMS AND PHRASES IN THE LEGISLATION - Beken, Шолан; Мurat, Асылбаев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article deals with the capacity and role of the state language, circumstances of uniform and exact use of commonly used in legislation terms and phrases, quality of the translation of certain words (including borrowed words), specific grammar, spelling peculiarities of the Kazakh language.